Keterikatan Manusia-Air dalam modernisasi Irigasi (Tinjauan Buku How Water Makes Us Human Engagements with The Materiality of Water) - Ernawati Ernawati (Jurnal Sosioteknologi, 2026)
The book “How Water Makes Us Human” broadly argues that the human relationship with water is co-constitutive, in that humans not only utilize water but are also materially and existentially shaped alongside it. Through the framework of New Materialities (NM), Attala demonstrates that human life is embedded within a broader material network, where the substance of the world is not merely a passive backdrop but an element that actively enables and configures human existence. This book highlights how this liquid matter—water—functions as a connecting medium that physically and conceptually unites the human body with the rest of the material world. The New Materialities perspective, as developed by Bennett, Coole & Frost, as well as Drazin & Küchler, understands life as the result of mutually influencing material interactions. This approach seeks to transcend the boundaries of individual entities and examines how material relationships produce specific forms of existence. New Materialities acknowledges that social and ecological phenomena are always complex and influenced by various factors, yet this complexity is rooted in the dynamics of matter itself, not merely in political or economic structures. New Materialities emphasizes the co-generative nature of relationships or “becoming-with,” asserting that the outcomes of these relationships always depend on the physical properties and capabilities of the materials involved.